2023
DOI: 10.1158/1078-0432.ccr-22-3136
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Axicabtagene Ciloleucel versus Standard of Care in Patients 65 Years of Age or Older with Relapsed/Refractory Large B-Cell Lymphoma

Abstract: Purpose: Older patients with relapsed/refractory (R/R) large B-cell lymphoma (LBCL) may be considered ineligible for curative-intent therapy including high-dose chemotherapy with autologous stem-cell transplantation (HDT-ASCT). Here, we report outcomes of a preplanned subgroup analysis of patients ≥65 years in ZUMA-7. Patients and Methods: Patients with LBCL refractory to or relapsed ≤12 months after first-line chemoimmunothe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…[8][9] A subgroup analysis of the ZUMA-7 study limited to patients 65 years of age or older showed a higher rate of ORR and CRR in the Axi-Cel group compared to the standard care group (ORR 88% vs 52%, respectively; CRR 75% vs 33%, respectively). 10 In particular, no grade 5 cytokine release syndrome or neurologic events occurred in this group of patients who are more fragile and at risk for complications. 10 The ZUMA-7 trial was preceded by the ZUMA-1 trial exploring the efficacy of Axi-Cel in third-line therapy.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…[8][9] A subgroup analysis of the ZUMA-7 study limited to patients 65 years of age or older showed a higher rate of ORR and CRR in the Axi-Cel group compared to the standard care group (ORR 88% vs 52%, respectively; CRR 75% vs 33%, respectively). 10 In particular, no grade 5 cytokine release syndrome or neurologic events occurred in this group of patients who are more fragile and at risk for complications. 10 The ZUMA-7 trial was preceded by the ZUMA-1 trial exploring the efficacy of Axi-Cel in third-line therapy.…”
mentioning
confidence: 74%
“…10 In particular, no grade 5 cytokine release syndrome or neurologic events occurred in this group of patients who are more fragile and at risk for complications. 10 The ZUMA-7 trial was preceded by the ZUMA-1 trial exploring the efficacy of Axi-Cel in third-line therapy. ZUMA-1 was a single-arm phase I/II study enrolling LBCL patients with refractory or relapsed disease after autologous stem cell transplantation; the patients received a target dose of 2x10 6 CAR-T cells per Kg of body weight after conditioning chemotherapy with fludarabine and cyclophosphamide.…”
mentioning
confidence: 74%
“…Other than biological risk factors, patients with advanced age (>65 years) and comorbidities who may not be suitable for autoSCT could be reasonable candidates for second‐line CAR T‐cell therapy (all three trials included ~30% of the patients in this age group). In the post hoc analysis of ZUMA‐7 which included elderly patients (age ≥ 65), median EFS was greater with axi‐cel than with SOC (21.5 months vs. 5 months; HR, 0.276; p < .0001) 25 . The PILOT study investigated the utility of liso‐cel as a second‐line treatment for patients with r/r DLBCL not intended for autoSCT 26 .…”
Section: Car T‐cell Therapies In Second Line Dlbclmentioning
confidence: 99%
“…CAR NK cells will release perforin and granzymes to kill tumor cells (c). Most CAR-T therapies consist of autologous T cells, whereas CAR-NK cell therapies can be generated from allogeneic donors with R/R DLBCL [69].…”
Section: Car-t Cell As Second-line Therapies For R/r Dlbclsmentioning
confidence: 99%